The US 19th and 20th century experiences: Lessons for the Eurozone crisis - Joshua Aizenman (University of California, Economics Department, 2012)
The evolution of institutions in the US and other unions provides clear lessons. There are large gains from buffering currency unions with a union-wide deposit insurance, and partial debt mutualisation. The credibility of a union deposit insurance scheme requires transparent funding and supervision, with a reliable backstopping mechanism. Establishing the credibility of such a scheme benefits from partial debt mutualisation and the formation of a dedicated union-level tax collection needed to serve these liabilities. Limited debt mutualisation does not preclude the existence of a vibrant independent debt market for the union's states, restricted by each state's tax revenue.
Keywords: 330